Language and philosophical problems - Stenlund, Sõren (Routledge, 1990)
In this book it will be show how various manifestations of this calculus conception are at the root of several conceptual and philosophical problems of current interest. It will be seen that many of these conceptual problems have roots crossing the current classification boundaries of a variety of philosophical problems. As a consequence, this study will be devoted to related problems in the philosophies of language, mathematics, and mind, and in the philosophical discussion of Artificial Intelligence